2021
DOI: 10.1126/sciadv.abb3673
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic drug screening in a human fibrosis model identified a novel class of antifibrotic therapeutics

Abstract: Innovative high-content screening platform identified N -(2-butoxyphenyl)-3-(phenyl)acrylamides as novel antifibrotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…1A). To analyze antifibrotic drug effects, we cotreated FC-stimulated hPCLS with the clinically approved antifibrotic drug nintedanib ( 3 ), as well as an N -(2-butoxyphenyl)-3-(phenyl)acrylamide (N23P) derivative of tranilast (CMP4), which we recently identified as an antifibrotic compound ( 24 ). After treatment, we performed scRNA-seq using the 10x Genomics Chromium platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). To analyze antifibrotic drug effects, we cotreated FC-stimulated hPCLS with the clinically approved antifibrotic drug nintedanib ( 3 ), as well as an N -(2-butoxyphenyl)-3-(phenyl)acrylamide (N23P) derivative of tranilast (CMP4), which we recently identified as an antifibrotic compound ( 24 ). After treatment, we performed scRNA-seq using the 10x Genomics Chromium platform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8). As a proof of concept, we analyzed the effects of the clinically approved antifibrotic drug nintedanib ( 3 ) and the tranilast-derivative CMP4, which we recently have identified as an antifibrotic drug candidate ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…We determined drug concentrations via a literature search, prioritizing concentrations that yielded significant effects in vitro in fibroblasts or similar cell types. The drugs with their respective concentrations are as follows: [0.25,1,2] µg/ml of anakinra (Kineret, SOBI Inc.), [1,5,10] µM valsartan (Sigma-Aldrich, SML0142-10MG), [0.2,1,2] µM BNP (Sigma-Aldrich, B5900-.5MG), [1,5,10]µM valsartan combos respectively with [0.2,1,2] µM BNP, [10,30,60]mM glutathione (Sigma-Aldrich, G4251-1G), [1,3,5] µM CW-HM12 (Cayman Chemical Company, 19480), [10,20,50] µM salbutamol (Sigma-Aldrich, S8260-25MG), [5,10,25] µM marimistat (Sigma-Aldrich, M2699-5Mg), [1,5,10] µM galunisertib (Selleck Chemicals, S2230), [12.5,25,50] µM fasudil (Sigma-Aldrich, CDS021620-10MG), [10,25,50 ]µM SB203580 (Sigma-Aldrich, S8307-1MG), [1,5,10] mg/mL pirfenidone (Sigma-Aldrich, P2116-10MG), [5,10,20] µM defactinib (MedChem Express, HY-12289A), [5,10,20] µM WH-4-023 (Sigma-Aldrich, SML1334-5MG), and 20 µM LY294002 (Selleck Chemicals, S1105). Cells were grown in these conditions for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…While high expression of these markers provides an initial indication of myofibroblast activation, traditional marker expression is inconsistent and does not fully capture the fibrotic response 7 . Recent studies of fibroblast phenotype have shown that fibroblasts exhibit high phenotypic heterogeneity across many facets in response to injury, and that phenotypic changes are also sensitive to drug perturbations [8][9][10][11] . Identifying drugs that regulate fibroblast signaling may provide targeted control of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The ECM deposition assay was carried in 384-well CellCarrier plates (PerkinElmer, #6007550), and modified procedures were performed based on the previously described (Gerckens et al, 2021) . Briefly, The plate was coated with 10 μg/mL FN1 (Sigma, # F1141-1MG) for 1 hour at RT before seeding cells.…”
Section: Ecm Depositionmentioning
confidence: 99%